Git and GitHub masterclass : fast-track your journey to Git. - T., Karthikeya (Packt Publishing, 2022)
Git is a Version Control System, whereas GitHub is a centralized repository to host the code, to enable team collaboration. In this course, you will learn about Git and GitHub and all the concepts pertaining to them. It will also cover the use cases and workflows that you need to know as a developer. In this hands-on course, you will start by understanding the need for a Version Control System and how Git operates and will learn how to install Git on your local systems. You will dive deep into Git by understanding the SHA1 Hashing algorithm, blob objects, Git internals, and Git Snapshot. You will explore everything about branches, merging, and three-way mergers in action and learn to perform rebase in VS code. You will also learn about stashing and its use cases and learn to retrieve a specific stash. Later, you will learn to collaborate effectively using GitHub. Concepts such as commits in GitHub, the README.md file, cloning a private repository, and adding project collaborators on GitHub will be covered. You will also explore how to create a remote branch and push changes using Git Bash and VSCode and learn to resolve conflicts on GitHub the right way. It goes on to cover Git fetch and understand its use cases and understand Git pull with the three-way merge. Branching strategy with a real-time scenario will be explained as well. By the end of the course, you will be able to fork the public repository and clone it to your local machine and learn about digital signatures as well as signed commits. What You Will Learn Understand the need for version control, Git, and branches in Git Understand the SHA1 Hashing algorithm Clone a private repository and add project collaborators on GitHub Learn to create a remote branch and push changes using Git Bash Learn to sync the forked repository with the original from the local repository Learn to make signed commits and verify them on GitHub Audience This course can be taken by people who are getting started with their developer journey. Managers/team leads who lead a project or someone who wants to get started with their DevOps journey can opt for this course. Passionate learners who want to upgrade their skills for better job prospects can take up this Git and GitHub masterclass course. No prior programming knowledge is needed to take up this course. About The Author Karthikeya T.: Teaching is an art in Karthikeya T.'s opinion. He believes it's the responsibility of the instructor to make sure that the student understands the concepts. He doesn't want to promote his decade and a half of experience in the industry. All his experience means nothing to him if he fails to teach his students in the way they understand. His primary focus is to teach the technology and ease our journey to a successful life.